2018
DOI: 10.1111/1744-7917.12588
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of genetically modified Lepidoptera‐resistant Brassica napus in biodiversity hotspots: Sicily as a theoretical model

Abstract: The general increase of the cultivation and trade of Bt transgenic plants resistant to Lepidoptera pests raises concerns regarding the conservation of animal and plant biodiversity. Demand for biofuels has increased the cultivation and importation of oilseed rape (Brassica napus L.), including transgenic lines. In environmental risk assessments (ERAs) for its potential future cultivation as well as for food and feed uses, the impact on wild Brassicaeae relatives and on non-target Lepidoptera should be assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…This period is then followed by a decrease both in abundance and specific richness of the communities, as observed in [52]. This peak in butterfly diversity also coincided with food availability due to the Mediterranean vegetation phenology [53][54][55][56]. The WAS and BUP after were mostly composed of early blooming Mediterranean species or nectariferous horticultural species that are very sensitive to summer drought leading to a drop in nectar availability after May.…”
Section: Impact Of Species Phenology On Resultsmentioning
confidence: 79%
“…This period is then followed by a decrease both in abundance and specific richness of the communities, as observed in [52]. This peak in butterfly diversity also coincided with food availability due to the Mediterranean vegetation phenology [53][54][55][56]. The WAS and BUP after were mostly composed of early blooming Mediterranean species or nectariferous horticultural species that are very sensitive to summer drought leading to a drop in nectar availability after May.…”
Section: Impact Of Species Phenology On Resultsmentioning
confidence: 79%
“…Against this background and to harmonise protection goals for ERA purposes as required by EFSA, effects by GM crops on non-target lepidopteran species in off-field areas need to be small to negligible. Clearly, for endangered or protected Lepidoptera occurring in protected sites or biodiversity hotspots within the agro-environment [133135], no additional adverse effects due to Bt maize cultivation should be tolerated at all (see also [22]).…”
Section: Resultsmentioning
confidence: 99%
“…In rapeseed Bt transgenic lines, it has been reported that there could be an exposure to the insecticidal protein of transgenic lines by diurnal pollinators Lepidoptera, as larvae (mainly of Pieridae) through the host and through pollen, and as adults via pollen and nectar. This could lead to a localized loss of biodiversity that requires exhaustive environmental risk assessments [158]. Similarly, the effects of silkworm (Bombyx mori) larvae with pollen from Bt Chinese cabbage have been studied.…”
Section: Progress On Transgenic Research In Beneficial Biotic Interactions Of Brassica Speciesmentioning
confidence: 99%